Pengaruh Kepemimpinan Visioner, Suasana Akademik dan Motivasi Kerja Terhadap Kinerja Dosen STMIK Binjai - Wijaya Wijaya; Indra Prasetia; Faisal Rahman Dongoran (UMSU, 2023)
This research is a quantitative research, which aims to determine the influence of leadership, school culture and empowerment on the work motivation of State Elementary School teachers in Sibolga. The sample of this study was 83 teachers with civil servant status. The research instrument was in the form of a questionnaire distributed to the research respondents. The results showed that the multiple regression equation simultaneously was Y = 15,757 + 0.156 X1 + 0.113 X2 + 0.636 X3. This positive regression line equation indicates that the better leadership (X1), school culture (X2) and empowerment (X3) will increase work motivation (Y), then Ha is accepted and H0 is rejected. Obtained the value of R square of 0.403. This means that the variables of leadership (X1), school culture (X2) and empowerment (X3) affect teacher motivation (Y) together by 40.3%, and the remaining 59.7% is determined by other reasons that are not researched